Peran Keterlibatan Suami Melalui Pengetahuan, Jumlah Anak dan Dukungan dalam Keberhasilan Pemberian ASI Eksklusif - Yuda, Rahmi Andrita (Universitas Mohammad Husni Thamrin, 2024)
Exclusive breastfeeding during the first six months of an infant’s life offers significant benefits for both the infant and mother. However, the coverage of exclusive breastfeeding in Indonesia remains below the national target. This study aimed to analyze the relationship between husbands' knowledge level, number of children, and husbands' support with exclusive breastfeeding practices in the working area of Puskesmas Pasar Rebo, East Jakarta. A cross-sectional design was used involving 52 respondents selected through one-stage cluster sampling. Data were collected using a structured questionnaire and analyzed using the chi-square test. Results showed that only 32.7% of mothers practiced exclusive breastfeeding. As many as 59.6% of husbands had poor knowledge, and 65.4% of breastfeeding mothers did not receive adequate support from their husbands. There were significant relationships between husbands’ knowledge (p = 0.001), number of children (p = 0.002), and husbands’ support (p = 0.001) with exclusive breastfeeding practices. These findings highlight the crucial role of husbands in breastfeeding success. Therefore, family-based interventions that enhance husbands’ knowledge and involvement are essential to improve exclusive breastfeeding coverage and support the achievement of national child health goal.